Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/ejic.201402767
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic Stability and Hydrogen Peroxide Activation of Zirconium‐Based Oxoclusters

Abstract: The hydrolytic stability of [Zr6(OH)4O4{O(O)CC(CH3)=CH2}12] (Zr6), and [Zr6O4(OH)4{O(O)CCH2CH=CH2}12]2·6[CH2=CHCH2C(O)OH] (Zr12) oxoclusters in different environments was thoroughly investigated by FTIR, Raman, and X-ray photoelectron spectroscopy (XPS). Specific information about the local structures around the Zr centers during the stability tests was achieved by in situ extended X-ray absorption fine structure (EXAFS) measurements, and the exact compositions were determined by inductively coupled plasma MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 110 publications
(66 reference statements)
5
48
0
Order By: Relevance
“…we observed that upon film deposition this material seems to lose the extra carboxylic acid molecules that are not covalently bonded to the inorganic core but that are occluded in the crystalline sample. [24] Their presence in the crystalline powder sample can be detected by a weight loss around 200 o C in the TGA, and in the IR spectrum ( Fig. 1a-b, C=O stretching at 1697 cm -1 and broad band between 2770 and 3515 cm -1 due to O-H stretching of the carboxylic acid, marked with asterisk).…”
Section: Lithographic Performancementioning
confidence: 95%
See 1 more Smart Citation
“…we observed that upon film deposition this material seems to lose the extra carboxylic acid molecules that are not covalently bonded to the inorganic core but that are occluded in the crystalline sample. [24] Their presence in the crystalline powder sample can be detected by a weight loss around 200 o C in the TGA, and in the IR spectrum ( Fig. 1a-b, C=O stretching at 1697 cm -1 and broad band between 2770 and 3515 cm -1 due to O-H stretching of the carboxylic acid, marked with asterisk).…”
Section: Lithographic Performancementioning
confidence: 95%
“…It is known that carboxylate ligands in oxoclusters can be displaced by water or by competing chelating agents. [24] XPS analyses shown below point in this direction and thus optimisation of spin-coating and sample handling is required for this molecular material. The trends in sensitivity were also observed in dense line pattern transfer ( Table 1).…”
Section: Lithographic Performancementioning
confidence: 99%
“…Originally, those carboxylic acids are not covalently bonded to the inorganic core but are occluded in the crystalline sample. 28 Their presence in the crystalline powder sample can be detected and in the IR spectrum [Figs. 1(a) and 1(b), C═O stretching at 1697 cm −1 and broadband between 2770 and 3515 cm −1 due to O─H stretching of the carboxylic acid, marked with asterisk] and it is further supported by the mass ratio between combustible organics and incombustible inorganic residue found in the TGA.…”
Section: Lithographic Performancementioning
confidence: 99%
“…Between these, PSE is believed to be a simple way to introduce unsaturated open sites while preserving the MOFs’ structural integrity and high porosity . In addition, it has been found that the formation of Zr IV ‐peroxo complexes by reaction of the Zr‐oxoclusters [Zr 6 O 4 (OH) 4 ] with oxidizing agents contributes to the sulfur oxidation in ODS, suggesting that a larger number of Zr IV sites can bring enhanced catalytic activity . UiO‐66, with its 12‐fold, fully connected hexanuclear Zr clusters, has been studied for ODS by Granadeiro et al, showing outstanding efficiency .…”
Section: Introductionmentioning
confidence: 99%